A survey on poorly known rainforest litter-dwelling spiders of Orchid Island (Lanyu, Taiwan) with the description of a new species (Araneae: Linyphiidae, Tetrablemmidae, and Theridiosomatidae) - Ballarin, Francesco; Yamasaki, Takeshi; Su, Yong-Chao (Zootaxa, 2021)
Representatives of some poorly known spider species collected in the rainforest litter of the Orchid Island (Taiwan) are illustrated and discussed here. A new species, Brignoliella tao sp. nov. (Fam. Tetrablemmidae), endemic to Orchid Island, is described based on both sexes. The previously unknown female of Theridiosoma triumphale Zhao & Li, 2012 (Fam. Theridiosomatidae), is described for the first time. Zoma taiwanica (Zhang, Zhu & Tso 2006) comb. nov., from the same family, is illustrated and its transfer from the genus Theridiosoma O. Pickard-Cambridge, 1879 to Zoma Saaristo, 1996 is proposed on the basis of morphological characters. Habitus and genitalia of the endemic species Gongylidioides angustus Tu & Li, 2006 (Fam. Linyphiidae) are also illustrated.